Untersuchungen zur Besiedlung und gegenwärtigen Waldnutzung im Hindukush/Karakorum.: Vorläufige Ergebnisse aus laufenden Arbeiten des DFG-Schwerpunktprogrammes Kulturraum Karakorum - Jacobsen, Jens-Peter; Schickhoff, Udo (ERDKUNDE, 1995)
Inferred from the evidence of irrigated cultivation as well as from the finds of datable material with indications of human activities, settlement in the central area of the Yasin valley (Eastem Hindukush) is assumed to have occured at least since the second century B.C. As a result, it is obvious that the last verifiable glacier advance down dose to the village Yasin had taken place at least 2200 years ago. However, pollen analyses so far indicate a much earlier beginning of settlement, because synanthropic species and crop plants increasingly appeared 3000 years ago. Thus, man has reshaped the natural environment for three millennia, at least. Nowadays, reinforced exploitation of the natural forest resources has been induced by the development of the road network in this high mountain region, leading to the ecological degradation of most forest stands. In some valleys more than half of all trees had been felled. Timber cutting concentrates on easily accessible valleys being opened up by four-wheel drive roads. The low degree of decay of most of the cut stumps gives evidence of the dose correlation between the extension of the road network and timber cutting in the past twenty years. Moreover, further complex relations exist between forest degradation and the change of the general socio-economic conditions. During the further course of this research project these relations have to be analysed.